Effect of 40% hydrogen peroxide on the bond strength of brackets at different time intervals. In vitro study. Tacna, 2016 - Sánchez Tito, Marco Antonio (2016)
Objective: to evaluate the effects of hydrogen peroxide at 40% as a bleaching agent on shear bond strength of metallic brackets bonded at several time intervals. Materials and methods: 60 upper premolar were randomly assigned to four groups of 15 units each. In group | brackets were bondedat1 hour after the bleaching, in group II the brackets were bonded after 7 days, and in the group III the brackets were bonded after 14 days, a group was used as a control, where bleaching agent was not applied. Shear bond strengths of all the brackets were tested with a Universal testing machine. ARI Index was used to evaluate the interface of bond fail. Results: the results showed that bleaching significantly reduced the bonding strength of the orthodontic brackets (p<0.05). The mean shear bond strength of group III (17.95 MPa) were not statistically different to the group control (18.03 MPa). In group and Il the values were lower (13.37 MPa, 13.58 MPa respectively). There were found significant differences in ARI index (p<0.05). ARI score 3 was observed in group control, what indicate that the fail interface was bracket/adhesive predominately. In group | the fail interface was more frequently in the enamel/adhesive interface. Conclusions: the use of hydrogen peroxide at 40% as a bleaching agent reduce the shear bond strength of metallic brackets. Values turn to normality after 14 days.